2005
DOI: 10.1007/s00125-005-1794-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria as a predictor of subsequent hospitalisation with urinary tract infection in diabetic adults: The Fremantle Diabetes Study

Abstract: Aims/hypothesis: We examined the prognosis of well-characterised community-based diabetic patients with asymptomatic bacteriuria (ASB). Methods: We studied 496 adults with type 1 or 2 diabetes participating in a prospective observational study. In addition to detailed clinical and laboratory data, a single mid-stream urine sample was taken for aerobic culture and antibiotic-sensitivity testing. ASB was defined as ≥10 5 colony-forming units/ml of one or two organisms without symptoms of urinary infection. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 11 publications
2
23
0
1
Order By: Relevance
“…The mean creatinine level did not differ in diabetic subjects with or without ASB in three cross-sectional surveys (pooled difference 0.21 μmol/l [95% CI −0.3 to 0.8]; P = 0.36) (7,11,19). Association of proteinuria and ASB was studied in three trials (10,19,20).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The mean creatinine level did not differ in diabetic subjects with or without ASB in three cross-sectional surveys (pooled difference 0.21 μmol/l [95% CI −0.3 to 0.8]; P = 0.36) (7,11,19). Association of proteinuria and ASB was studied in three trials (10,19,20).…”
Section: Resultsmentioning
confidence: 94%
“…Although ASB has been found to associate with increased risk of hospitalization for urosepsis in a prospective observational study among women with diabetes (7), the treatment of ASB in one randomized controlled trial did not reduce the risk of symptomatic urinary tract infection (8). Associations between ASB, metabolic control of diabetes, and impaired renal function have been brought up repeatedly (915).…”
mentioning
confidence: 99%
“…17,70 However, investigators found that the treatment among women hospitalized for diabetes has not reduced the pervasiveness of asymptomatic bacteriuria. 71 Research studies also substantiated the relation between asymptomatic bacteriuria, diabetes and impaired kidney function. 72,73 Many other researchers have attempted to unveil the association between asymptomatic bacteriuria and diabetes and have successfully revealed the alliance of asymptomatic bacteriuria and the host factors among women with diabetes.…”
Section: Diabetes and Utimentioning
confidence: 89%
“…A number of predisposing factors for ASB have been reported. In most [99][100][101][102] but not all [103] studies, there is no relationship between glycaemic control and ASB. Chronic complications such as nephropathy and neuropathy have been associated with ASB in type 1 but not type 2 diabetes [99,104], a pattern that holds for longer diabetes duration [104].…”
Section: Urinary Tract Infectionsmentioning
confidence: 97%